Effect of Fed Rate and Inflation on Automotive Stock Index in Indonesia (2019–2023): Pengaruh Suku Bunga The Fed dan Inflasi terhadap Indeks Saham Otomotif di Indonesia 2019–2023 - Mulyani, Sri; Dewantoro, Suryo Hadi; Santoso, Aditya; Setiawati, Setiawati (Jurnal Bisnis dan Ekonomi, 2025)
Abstract: Objective: This study aims to analyse the effect of the Fed interest rate and inflation on the Composite Stock Price Index (IHSG) of automotive companies on the Indonesia Stock Exchange (IDX) for the period 2019-2023. Methodology: The research method used a quantitative approach with secondary data from the Federal Reserve and IDX. The sample consisted of seven automotive companies selected using purposive sampling. Data analysis included classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation) and linear regression tests. Research Findings: The results indicate that, both partially and simultaneously, the Fed interest rate and inflation do not have a significant effect on the IHSG (Sig. > 0.05). The coefficient of determination (R²) of 7.9% indicates that 92.1% of the IHSG's movement is influenced by factors outside the model, such as company performance or domestic policy. This finding is consistent with previous studies stating that external factors such as the Fed interest rate and global inflation have a limited impact on the automotive sector IHSG. Keywords: Fed interest rates, inflation, Composite Stock Price Index